BRIDGING THE GENDER GAP: A CRITICAL STUDY OF WOMEN’S RESERVATION IN THE INDIAN PARLIAMENT - Singh, Anju; Devi, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The passage of the amendment bill to introduce 33% reservation for women in Parliament and state assemblies represents a significant advancement toward the political empowerment of women in India. The issue of women’s reservation in India is unique because the Indian Constitution already provides reservations for Scheduled Castes (SC), Scheduled Tribes (ST), and Other Backwards Classes (OBC). The 73rd and 74th amendments to the Constitution ensure that women have 33% representation in local self-government. It is essential to address the social barriers that impede women’s equal representation in Indian society, which is patriarchal in nature. (Rai & Sharma, 2000). Reserving seats for women will drive significant change. These reservations aim to establish an equal opportunity for all citizens. Gender inequality continues to permeate political decision-making, highlighting an urgent need for more women leaders to step forward. Women can significantly influence policies and shape a more equitable future by increasing representation. Let us empower women to rise and make their voices heard in the halls of power. This paper seeks to analyse the advantages and disadvantages of women’s reservation from the government’s perspective, explore the reasons behind the passage of this bill in parliament, and provide a comprehensive background on the Women’s Reservation Bill. The author will present findings supported by secondary data to elucidate these points.